2021
DOI: 10.1186/s43058-021-00228-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrating PrEP delivery in public health family planning clinics: a protocol for a pragmatic stepped wedge cluster randomized trial in Kenya

Abstract: Background Adolescent girls and young women account for a disproportionate fraction of new HIV infections in Africa and are a priority population for HIV prevention, including provision of pre-exposure prophylaxis (PrEP). Anchoring PrEP delivery to care settings like family planning (FP) services that women already access routinely may offer an efficient platform to reach HIV at-risk women. However, context-specific implementation science evaluation is needed. Met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…We found that individuals having partners living with HIV and those with sexual behaviours likely to put them at elevated risk for HIV were more likely to exhibit high continuation and persistence patterns on PrEP. Consistent with previous studies [ 28 , 29 , 30 , 31 ], these findings indicate that individuals continue reasonably well on PrEP when they perceive to be at risk for HIV—like having a partner living with HIV. Thus, efforts to identify strategies that support the recognition of HIV risk and normalization of PrEP use are needed to help persons navigate their decisions about PrEP use and HIV prevention preferences.…”
Section: Discussionsupporting
confidence: 90%
“…We found that individuals having partners living with HIV and those with sexual behaviours likely to put them at elevated risk for HIV were more likely to exhibit high continuation and persistence patterns on PrEP. Consistent with previous studies [ 28 , 29 , 30 , 31 ], these findings indicate that individuals continue reasonably well on PrEP when they perceive to be at risk for HIV—like having a partner living with HIV. Thus, efforts to identify strategies that support the recognition of HIV risk and normalization of PrEP use are needed to help persons navigate their decisions about PrEP use and HIV prevention preferences.…”
Section: Discussionsupporting
confidence: 90%
“…PrEP was initially delivered in HIV clinics, which worked well to increase PrEP uptake among HIV‐uninfected partners in HIV serodifferent couples through integrated care programmes delivering both ART and PrEP [ 30 , 31 ]. Increasingly, PrEP is being integrated into other service points to cater for different populations, such as in antenatal clinics [ 32 , 33 ], family planning clinics [ 33 ], post‐abortion care [ 34 ] and STI clinics [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The desire to stay healthy HIV free and bare HIV negative children has been noted as motivator to be retained on PrEP [ 38 ].Relatedly, the desire to stay healthy and maintain earning potential so as to take care of their children has also been cited as a motivator to being retained on PrEP [ 39 ]. This further emphasizes the need to integrate PrEP into sexual and reproductive health services [ 40 ]. FSW on PrEP that come to clinics for contraceptive counseling or for their next dose of injectable contraceptives get an opportunity to hear PrEP reinforcing messages [ 39 ].…”
Section: Discussionmentioning
confidence: 99%